Comparative in vitro activities of selected antimicrobial agents against Aeromonas species and Plesiomonas shigelloides. - Reinhardt, J F (1985)
The in vitro antimicrobial susceptibilities of fecal isolates of Aeromonas caviae, Aeromonas hydrophila, Aeromonas sobria, and Plesiomonas shigelloides were tested by agar dilution. This in vitro study suggested that ciprofloxacin, enoxacin, norfloxacin, tetracycline, and trimethoprim-sulfamethoxazole might be effective oral agents for treatment of diarrhea involving Aeromonas spp. or P. shigelloides.